2018
DOI: 10.1007/s12034-018-1625-z
|View full text |Cite
|
Sign up to set email alerts
|

A first method for preparation of biodegradable fibrous scaffolds containing iodine on the fibre surfaces

Abstract: Fibrous electrospun scaffolds made of poly(L-lactic acid) (PLLA) and poly(ε-caprolactone) (PCL) were modified with iodine using 'solvent/non-solvent' treatment of the polymer through two-step process. At the first step, the scaffolds were treated with mixture of toluene and ethanol for pre-swelling of the fibre surfaces. Then, treated scaffolds were exposed to iodine vapours to entrap iodine on the polymer surface. Concentration of iodine in obtained materials was measured by means of UV-spectrophotometry. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A promising approach for modifying the surface of biodegradable polyesters involves treatment of the polymer with a mixture of organic solvents to partially swell its surface [ 41 , 42 , 43 ]. It was shown that a mixture of toluene and ethanol has no destructive effect on the PCL scaffold structure and allows non-covalent immobilization of gelatin and iodine.…”
Section: Resultsmentioning
confidence: 99%
“…A promising approach for modifying the surface of biodegradable polyesters involves treatment of the polymer with a mixture of organic solvents to partially swell its surface [ 41 , 42 , 43 ]. It was shown that a mixture of toluene and ethanol has no destructive effect on the PCL scaffold structure and allows non-covalent immobilization of gelatin and iodine.…”
Section: Resultsmentioning
confidence: 99%
“…A promising approach for modifying the surface of PCL involves treatment of the polymer with a mixture of organic solvents to partially swell its surface [21]. The swelled surface layer of the polymer can adsorb biologically active molecules and particles from the contacting medium.…”
Section: Introductionmentioning
confidence: 99%